AKTIVITAS ANTIDIABETES EKTRAK ETIL ASETAT DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) - Dede Sukandar; Sandra Hermanto; Imamah Al Mabrur (Jurnal Kimia Terapan Indonesia, 2010)
This research done to know activity antidiabetes from fragrant screw pine leaf ethyl acetate extract (Pandanus amaryllifolius Roxb.) applies method aglukosidase. Extract is made by the way ofmaceration to apply ethyl acetate. Test antidiabetes is done by using enzyme a-glukosidase and PNP-a-D-glukopiranosida. Fragrant screw pine leaf ethyl acetate extract haves the character of antidiabetes with resistance activity, IC50 value as 94,23 ppm. Result of GCMS identification shows fragrant screw pine leaf ethyl acetate extract contains active compound of its the fatty acid and deriuaies, terpenoids, and steroid.Keyword : Antidiabetes, Ekstrak Etil Asetat, Pandanus amaryllifolius Roxb, a-glukosidase, PNP-a-D-glukopiranosida.